给定 $T$ 个询问,每次询问给定 $k$,求
$$ \sum_{i=1}^{2k}\text{gcd}(k+i^2,k+(i+1)^2) $$
$$ (k+i^2,k+(i+1)^2)=(k+i^2,2i+1)=(4k+4i^2,2i+1)=(4k+1+(2i+1)\ast(2i-1),2i+1)=(4k+1,2i+1) $$
于是题目转化为求
$$ \sum_{i=1}^{2k}\text{gcd}(4k+1,2i+1) $$
记 $f(n)=\sum_{i=1}^n\text{gcd}(n,i),g(n)=\sum_{i=1}^n\text{gcd}(n,i)[2\mid i]$,于是有
$$ g(4k+1)+g(4k+1)=\sum_{i=1}^{2k}\text{gcd}(4k+1,2i)+\sum_{i=1}^{2k}\text{gcd}(4k+1,4k+1-2i)=f(4k+1)-(4k+1) $$
于是有
$$ \sum_{i=1}^{2k}\text{gcd}(4k+1,2i+1)=f(4k+1)-1-g(4k+1)=f(4k+1)-1-\frac{f(4k+1)-(4k+1)}2 $$
接下来考虑计算 $f$,有
$$ f(n)=\sum_{d\mid n} d\sum_{i=1}^n[\text{gcd}(n,i)=d]=\sum_{d\mid n} d\sum_{i=1}^n[\text{gcd}(\frac nd,\frac id)=1]=\sum_{d\mid n} \varphi(\frac nd)d $$
于是可以 $O(k\log k)$ 预处理。